Non-surgical management of patients with ectopic pregnancy: A review - Yulia E. Dobrokhotova; Tamara N. Belousova; Ekaterina I. Borovkova; Nikolai I. Sovaev; Vera D. Egorushkina; Anastasia D. Kladnitskaya; Anna Ermakova (IP Berlin A.V., 2023)
An ectopic pregnancy is a medical emergency. Currently, surgery is the main method of therapy, and non-surgical management with methotrexate is considered an acceptable alternative. Methotrexate is a folic acid antagonist and has an inhibitory effect on the proliferation of trophoblast cells. There are various methotrexate regimens; the choice is based on the level of β-subunit of human chorionic gonadotropin, the location of the ectopic pregnancy and the patient's adherence to treatment. Therapy of ectopic tubal pregnancy with methotrexate is an effective and safe alternative to surgical treatment, does not affect the ovarian reserve and preserves the woman's fertility.